Thyroid profile in depression: a cross-sectional study from North-East India - Hazarika, Jyoti; Kalita, Kamal N.; Sharma, Mohan; Saikia, Shilpi; Patangia, Priyanka; Hazarika, Pranabjyoti; Sarmah, Anil C. (International Journal of Research in Medical Sciences, 2017)
Background: Thyroid function disorder is a common feature in depression, with mixed type of response. Some cases are associated with hyperthyroidism and most commonly hypothyroidism. Unipolar and bipolar depressions are also related differently in consideration to thyroid status. This study comprises of assessment of the thyroid disorder prevalence in depressive patients and comparative analysis among unipolar and bipolar groups. Methods: Study consisted of 161 unipolar and 160 bipolar cases of depression as diagnosed by ICD 10 criteria supported by MINI. Thyroid profiling was done against common thyroid hormones TSH, T3, T4 and FT4 by standard method. Results: Gender wise males were dominant with majority in bipolar group in the younger age group. Most of the cases were normal with few hyperthyroid and hypothyroid cases. Bipolar group comprised the majority of overt hyperthyroid, overt hypothyroid and subclinical hyperthyroid cases, whereas unipolars were more in the subclinical hypothyroid category. Conclusions: This study concludes that differences exist in the thyroid response among the unipolar and bipolar depression group, more prominent numbers of hypothyroidism in unipolar group.